Rehabilitative treatment of cleft lip and palate: experience of the Hospital for Rehabilitation of Craniofacial Anomalies - USP (HRAC-USP) - part 3: Oral and Maxillofacial Surgery - José Alberto de Souza Freitas; Daniela Gamba Garib; Ivy Kiemle Trindade-Suedam; Roberta Martinelli Carvalho; Thais Marchini Oliveira; Rita de Cássia Moura Carvalho Lauris; Ana Lúcia Pompéia Fraga de Almeida; Lucimara Teixeira das Neves; Renato Yassutaka Faria Yaedú; Simone Soares; Reinaldo Mazzottini; João Henrique Nogueira Pinto (University of São Paulo, 2012)
This paper presents the treatment protocol of maxillofacial surgery in the rehabilitation process of cleft lip and palate patients adopted at HRAC-USP. Maxillofacial surgeons are responsible for the accomplishment of two main procedures, alveolar bone graft surgery and orthognathic surgery. The primary objective of alveolar bone graft is to provide bone tissue for the cleft site and then allow orthodontic movements for the establishment of an an adequate occlusion. When performed before the eruption of the maxillary permanent canine, it presents high rates of success. Orthognathic surgery aims at correcting maxillomandibular discrepancies, especially anteroposterior maxillary deficiencies, commonly observed in cleft lip and palate patients, for the achievement of a functional occlusion combined with a balanced face.